(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
Rapidly urbanizing regions usually experience urban heat islands with the attendant environmental and public health challenges. This study has used a low-cost LILYGO T-SIM7000G board with BME280 as a sensor to assess the UHI Index and compare such results with those obtained from the Copernicus ERA5-Land reanalysis data. The result shows a bias of about 1.36 in the UHI Index against the ERA5-Land data; this bias can be mitigated by applying a corrective offset. It was also observed that the ambient temperature in Lafia city has been consistently increasing between the years 1980 and 2024 by about 0.017 oC per year, with the highest increase recorded in the year 2024. The highest diurnal value of the UHI Index was observed around 1500 hours, while the lowest nighttime value was observed at around 0600 hours; this finding agrees with results as observed in other studies. This study has shown the importance of adopting low-cost components in monitoring environmental variables such as the UHI Index in low-income areas of the world, where funding may pose problems.